Barriers And Driving Factors of The Acceptance of Covid-19 Vaccination Program in The Working Area of The Bola Community Health Center, Sikka Regency - Dua, Katarina; Riwu, Yuliana Radja; Ndun, Helga J.N. (Media Kesehatan Masyarakat, 2024)
The COVID-19 vaccination program is an existing program to limit the transmission of COVID-19 disease. The problem lies with the community, such as topographical access to areas and services. The vaccination process at the Bola Health Center is ongoing, besides that there are still some people who have not received the vaccination program. This study aims to determine the barriers and factors driving the acceptance of the COVID-19 vaccination program in the working area of the Bola Health Center. This type of research is a qualitative research with a phenomenological approach. The number of informants was 22 people consisting of 10 key informants who received the COVID-19 vaccination and 10 key informants who had not received the COVID-19 vaccination and the supporting informants consisted of the head of the puskesmas and the manager of the COVID 19 vaccination program. The method used was purposive sampling , namely determine the sample with certain considerations. The results show that there are obstacles in receiving the COVID-19 vaccination, namely fear and doubt about the post-vaccination side effects that can be fatal and even cause death, loss of confidence, confidence in the effectiveness and safety of vaccines and public access to services. The reason people receive the COVID-19 vaccination is internal factors such as the intention of the informant, namely as a way to prevent and protect themselves from the risk of COVID-19 transmission. External factors, namely there are regulations from an agency, both universities and the government, requiring informants to have a COVID-19 vaccine card.